Ionized calcium serum evaluation in unilateral thyroidectomized cats - Corgozinho, Katia Barão (2015)
ABSTRACT. Corgozinho K.B., Cunha S.C.S., Neves A.P., Belchior C., Damico C.B., Silva C.A., Souza H.J.M.& Ferreira A.M.R. [Ionized calcium serum evaluation in unilateral thyroidectomized cats.] Avaliação do cálcio ionizado em gatos submetidos a tireoidectomia unilateral. Revista Brasileira de Medicina Veterinária 37(4):345-349, 2015. Pós-Graduação em Clínica e Reprodução Animal, Faculdade de Veterinária, Universidade Federal Fluminense, Rua Vital Brasil Filho, 64, Niterói, RJ 24230-340, Brasil. E-mail: katia.barao@gmail.com Seventeen hyperthyroid cats with cervical palpable nodules were submitted to clinical and laboratorial examination and they were prepared to surgery. Unilateral thyroparathyroidectomy with parathyroid gland autotransplantation was performed. Concentrations of serum urea, creatinine, alkaline phosphatase, alanine aminotransferase, phosphorus, potassium, total thyroxine and hematologic profile were determined before and seven days after surgery. Blood samples for serum ionized calcium concentration were collected before and after surgery on days 1, 2, 7, 15, 21. All cats had ionized calcium concentration within the reference range before surgery. Serum calcium concentration fell significantly in all cats within 24 hours after surgery. Hypocalcemia occurred in two cats without clinical signs. Ionized calcium concentration decreased after surgery and returned to normal levels on day 7 postoperatively. The results of this study suggest that calcium concentration must be measured before surgery in cats submitted to thyroidectomy even if they are submitted to unilateral technique.